Sensitivity and Resilience to Predator Stress-Enhanced Ethanol Drinking Is Associated With Sex-Dependent Differences in Stress-Regulating Systems - Alavi, Mehrdad; Ryabinin, Andrey E.; Helms, Melinda L.; Nipper, Michelle A.; Devaud, Leslie L.; Finn, Deborah A. (Frontiers in Behavioral Neuroscience, 2022)
Stress can increase ethanol drinking, and evidence confirms an association between post-traumatic stress disorder (PTSD) and the development of alcohol use disorder (AUD). Exposure to predator odor is considered a traumatic stressor, and predator stress (PS) has been used extensively as an animal model of PTSD. Our prior work determined that repeated exposure to intermittent PS significantly increased anxiety-related behavior, corticosterone levels, and neuronal activation in the hippocampus and prefrontal cortex in naïve male and female C57BL/6J mice. Intermittent PS exposure also increased subsequent ethanol drinking in a subgroup of animals, with heterogeneity of responses as seen with comorbid PTSD and AUD. The present studies built upon this prior work and began to characterize “sensitivity” and “resilience” to PS-enhanced drinking. Ethanol drinking was measured during baseline, intermittent PS exposure, and post-stress; mice were euthanized after 24-hour abstinence. Calculation of median and interquartile ranges identified “sensitive” (> 20% increase in drinking over baseline) and “resilient” (no change or decrease in drinking from baseline) subgroups. Intermittent PS significantly increased subsequent ethanol intake in 24% of male (60%) and in 20% of female (71%) C57BL/6J mice in the “sensitive” subgroup. Plasma corticosterone levels were increased significantly after PS in both sexes, but levels were lower in the “sensitive” versus “resilient” subgroups. In representative mice from “sensitive” and “resilient” subgroups, prefrontal cortex and hippocampus were analyzed by Western Blotting for levels of corticotropin releasing factor (CRF) receptor 1, CRF receptor 2, CRF binding protein, and glucocorticoid receptor, vs separate naïve age-matched mice. In prefrontal cortex, CRF receptor 1, CRF receptor 2, CRF binding protein, and glucocorticoid receptor levels were significantly higher in “sensitive” vs naïve and “resilient” mice only in females. In hippocampus, CRF receptor 1, CRF receptor 2 and glucocorticoid receptor levels were significantly lower in “resilient” vs naïve and “sensitive” mice across both sexes. These results indicate that sex strongly influences the effects of ethanol drinking and stress on proteins regulating stress and anxiety responses. They further suggest that targeting the CRF system and glucocorticoid receptors in AUD needs to consider the comorbidity of PTSD with AUD and sex of treated individuals.